Some Wave Simulation Properties of the (2+1) Dimensional Breaking Soliton Equation - Aksan, Emine Nesligul; Bulut, Hason; Kayhan, Mirac (E D P Sciences, 2017)
In this paper, we apply an efficient method which is improved Bernoulli sub-equation function method (IBSEFM) to (2+1) dimensional Breaking Soliton equation. It gives some new wave simulations like complex and exponential structures. We test whether all structures verify the (2+1) dimensional Breaking Soliton model. Then, we draw three and two dimensional plane by using Wolfram Mathematica 9.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY
Keywords: Complex